Exporting the Nordic children’s ’68: the global publishing scandal of The Little Red Schoolbook - Heywood, Sophie; Strandgaard Jensen, Helle (Barnboken, 2018)
The Little Red Schoolbook (1969) was one of the most well-travelled media products for children from ’68 aimed at children, and it was certainly the most notorious. Over the course of a few years (1970–2) it was translated and published in Belgium, Finland, France, Great Britain, the Federal Republic of Germany, Greece, Iceland, Italy, the Netherlands, Norway, Sweden and Switzerland, it also circulated freely in Austria and Luxembourg, and reached beyond Europe to countries including Australia, Japan and Mexico. It led to an obscenity trial in Great Britain, nearly toppled the Australian government, and caused a global publishing scandal. This essay therefore looks at the Scandinavian children’s ’68 in its international context, via a transnational, comparative analysis of the reception of the LRSB, in order to examine how ‘68 counterculture and ideas of childhood clashed and converged in the West around 1970. It asks: what can the publishing history of the LRSB tell us about the distinctive features of children’s media in Scandinavia at this time?